2022
DOI: 10.1186/s43042-022-00223-x
|View full text |Cite
|
Sign up to set email alerts
|

In-silico analysis unravels the structural and functional consequences of non-synonymous SNPs in the human IL-10 gene

Abstract: Background Interleukin-10 (IL-10) is an anti-inflammatory cytokine that affects different immune cells. It is also associated with the stimulation of the T and B cells for the production of antibodies. Several genetic polymorphisms in the IL-10 gene have been reported to cause or aggravate certain diseases like inflammatory bowel disease, rheumatoid arthritis, systemic sclerosis, asthma, etc. However, the disease susceptibility and abnormal function of the mutated IL-10 variants remain obscure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…SNPs can affect the binding interaction of RNA-protein by modification of secondary structure of RNA ( 52 , 53 ). Additionally, SNPs can affect both gene expression level of the specific protein or its binding with transcription factors ( 54 , 55 ). In all previously mentioned mechanisms, these can lead to modifications in either function or structure of the translated proteins (folding) and related metabolic pathways such as increased cell proliferation, protein dimerization and activation of a number of mediators ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs can affect the binding interaction of RNA-protein by modification of secondary structure of RNA ( 52 , 53 ). Additionally, SNPs can affect both gene expression level of the specific protein or its binding with transcription factors ( 54 , 55 ). In all previously mentioned mechanisms, these can lead to modifications in either function or structure of the translated proteins (folding) and related metabolic pathways such as increased cell proliferation, protein dimerization and activation of a number of mediators ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rate of Different Cancer Patients. The Kaplan-Meier Plot (https://kmplot.com/analysis/) [51] is an online tool that estimates the time of death, and this event may have a substantial inference while using these analytics for clinical decisions, medical policies, and also resource provision [52]. This plot is able to perform proportional survival analysis utilizing the data produced by genomic, transcriptomic, or proteomic investigations [51].…”
Section: Predicting Effects Of Met Deregulation On the Survivalmentioning
confidence: 99%
“…Proteins. Protein-protein interactions were investigated to interpret all functional interactions among cellular proteins [52]. The STRING database prediction showed that MET protein has interaction with other 10 proteins (Figure 10, Table 4) whose functions also might be interrupted by these mutations.…”
Section: Analysis Of Effects Of Deleterious Mutations On Othermentioning
confidence: 99%